2022
DOI: 10.3389/fpls.2022.1019966
|View full text |Cite
|
Sign up to set email alerts
|

Sown alfalfa pasture decreases grazing intensity while increasing soil carbon: Experimental observations and DNDC model predictions

Abstract: IntroductionGrasslands are the most important land use in China and have experienced extensive degradation in the past few decades due to overgrazing. However, regionally viable solutions to grazing intensity alleviation remained elusive to date.MethodsHere, we evaluated the grazing intensity effects of sown alfalfa pastures in northern China using an experiment-modeling combined approach that involved six sites in field experiments and five provinces in DNDC modeling of sown alfalfa pasture’s forage productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Moreover, government assistance is also needed in the selection and management of available climate-resilient germplasm resources. Recent research indicated that, for example, winter-hardy, indigenous species of alfalfa may provide both adaptation and mitigation benefits for northern grasslands in China [62,63]. In this context, the most important implication of our results is that climate adaptation is currently a more important and, thus, a more demanding task than climate mitigation, suggesting that the focus of grassland management efforts, including ecological restoration programs, should aim to make the entire grassland-livestock system more climate-resilient.…”
Section: Policy and Management Implicationsmentioning
confidence: 99%
“…Moreover, government assistance is also needed in the selection and management of available climate-resilient germplasm resources. Recent research indicated that, for example, winter-hardy, indigenous species of alfalfa may provide both adaptation and mitigation benefits for northern grasslands in China [62,63]. In this context, the most important implication of our results is that climate adaptation is currently a more important and, thus, a more demanding task than climate mitigation, suggesting that the focus of grassland management efforts, including ecological restoration programs, should aim to make the entire grassland-livestock system more climate-resilient.…”
Section: Policy and Management Implicationsmentioning
confidence: 99%
“…On the one hand, there is a good chance that the dual goals of grassland utilization and conservation can be simultaneously met under these management schemes (Tälle et al, 2016;Li et al, 2022). On the other hand, although previous research suggested that diversity-productivity synergy could be fulfilled via, e.g., competition mediation (Peintinger and Bergamini, 2006;Fagundez, 2016) and plant-soil interactions (Storkey et al, 2015;Xu et al, 2022b), it is still unclear how this synergy can be reliably triggered and temporally sustained. More research is therefore needed.…”
Section: Priorities For Future Researchmentioning
confidence: 99%
“…LOS change in croplands has significant implications for climate change mitigation, adaptation, crop yield, and food security [14][15][16][17][18]. Moreover, process-based crop models were developed and fine-tuned to crop cycles observed in the field [19,20]. It is thus a prerequisite to calibrate satellite-derived phenology to ground observations before it can be spatially assimilated by these models [21][22][23].…”
Section: Introductionmentioning
confidence: 99%